Superior Performance Competencies Achieved Through Destination Imagination Experiences - Ward, James G; Ward, Yaprak Dalat; Wells, Johnny; Bejot, Kimberly (Archives of Business Research, 2023)
Today’s workforce not only requires specific content-area knowledge and skills achieved through formal education but also, and most critically, superior performance competencies including distinguishable behaviors. While formal education prioritizes easily detectable and measurable content-specific knowledge and skills, superior performance competencies such as cognitive, affective, and motivational skills remain secondary unless students engage in extracurricular activities in real-world settings. This qualitative study investigated the phenomenon of achieving an array of superior performance competencies through learning by doing, at one of the 2023 Destination Imagination events. This study marked the first fieldwork in which the principal researcher directly observed the event in its natural setting. Data were collected, analyzed, and interpreted concurrently during the event by means of observations, ordinary conversations, and an informal interview. The inductive data analysis included analytic memos, and midway hypothesis coding which confirmed the significance of immersing in such activities and resulted in two major findings: 1) participating in such meaningful real-world activities cultivates distinctive behaviors that drive exceptional performance, positioning participants to stand out among their peers; and 2) this involvement also equips students with the capabilities to excel upon entering the workforce, ensuring superior employee performance in their roles.